PERAMALAN KAPASITAS BATERAI PADA KENDARAAN LISTRIK DENGAN METODA COULOMETRI - Kaloko, Bambang Sri (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
This article proposes a new coulometric approach to calculate the state of charge of a lead acid battery in electric vehicles. The main existing state of charge algorithms have two major defects: a state of charge definition not adapted to electric vehicle ap-plications and the nonoptimal use of static performance of the accumulator to estimate its state under dynamic stresses. In order to improve these two weaknesses, we propose a new coulometric algorithm linked to the performance of the electric vehicle and where the ampere hours virtually discharged are obtained by applying statistical equivalence coefficients to the real current profile. The evaluation of this new algorithm on real dis-charges reveals a significant improvement with less than 5% errors in all cases studied.